2016
DOI: 10.1016/j.joca.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling in postnatal joint chondrocytes, but not subchondral osteoblasts, is required for articular cartilage and joint maintenance

Abstract: Objective Notch signaling has been identified as a critical regulator in cartilage development and joint maintenance, and loss of Notch signaling in all joint tissues results in an early and progressive osteoarthritis (OA)-like pathology. This study investigated the targeted cell population within the knee joint in which Notch signaling is required for normal cartilage and joint integrity. Methods Two loss-of-function mouse models were generated with tissue-specific knockout of the core Notch signaling compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 46 publications
(56 reference statements)
2
24
0
Order By: Relevance
“…In one study, Rbpj knockout in limb mesenchymal progenitor cells using Prx1-Cre, or in adult chondrocytes using Col2a1-Cre ERT2 , promoted OA development within 8 months without surgical induction [26]. Similar results have been reported by the same group using Acan-Cre ERT2 and Rbpj-flox mice [27]. Interestingly, fibrotic cells and high levels of Mmp13 are observed in the superficial zone of Rbpj-knockout cartilage [27].…”
Section: Notch Signallingmentioning
confidence: 57%
“…In one study, Rbpj knockout in limb mesenchymal progenitor cells using Prx1-Cre, or in adult chondrocytes using Col2a1-Cre ERT2 , promoted OA development within 8 months without surgical induction [26]. Similar results have been reported by the same group using Acan-Cre ERT2 and Rbpj-flox mice [27]. Interestingly, fibrotic cells and high levels of Mmp13 are observed in the superficial zone of Rbpj-knockout cartilage [27].…”
Section: Notch Signallingmentioning
confidence: 57%
“…Numerous signaling pathways have been identified that regulate both cell cycle and chondrocyte hypertrophy, including BMP, TGF-β and Wnt. Recently, we identified the Notch signaling pathway as a critical regulator of chondrocyte hypertrophy, although it appears to regulate this process in an indirect manner 8 9 10 11 .…”
mentioning
confidence: 99%
“…While continuity of developmental programs may play a role in joint maintenance, there also appear to be factors with specific postnatal requirements at the joint, including Notch signaling, PRG4, and ERRFI1 . The Notch pathway has been implicated in progenitor maintenance in a variety of contexts, including a role for inhibiting cartilage differentiation in mice and zebrafish .…”
mentioning
confidence: 99%
“…The Notch pathway has been implicated in progenitor maintenance in a variety of contexts, including a role for inhibiting cartilage differentiation in mice and zebrafish . Notch1 is expressed at postnatal joints in mice, and conditional deletion of the essential Notch effector RBP‐Jk in either limb mesenchyme using Prx1 ‐Cre or postnatal chondrocytes using Col2a1 ‐CreER results in progressive joint cartilage degeneration and other osteoarthritic phenotypes . The miR‐140 is the major miRNA expressed in articular cartilage of murine joints, and deletion of miR‐140 predisposed mice to age‐related osteoarthritis of the knee without affecting joint specification .…”
mentioning
confidence: 99%